2013
DOI: 10.1017/s1368980013000323
|View full text |Cite
|
Sign up to set email alerts
|

Identification of lifestyle patterns associated with obesity and fat mass in children: the Healthy Growth Study

Abstract: Objective: To investigate possible associations of lifestyle patterns with obesity and fat mass in children. Design: Cross-sectional epidemiological study. Principal component analysis was used to identify lifestyle patterns. Setting: Primary schools from four regions in Greece. Subjects: A total of 2073 schoolchildren (aged 9-13 years). Results: Children in the fourth quartile of the lifestyle pattern combining higher dairy foods with more adequate breakfast consumption were 39?4 %, 45?2 % and 32?2 % less lik… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
76
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(80 citation statements)
references
References 49 publications
3
76
0
1
Order By: Relevance
“…According to this theory, one way to reduce the currently observed high prevalence of obesity, involving lifestyle-related behaviors, is the reduction in the consumption of high energy-dense and nutrientpoor foods [31]. The lifestyle patterns of the Portuguese children were similar to those observed among Greek children and adolescents [19,22,23]. Yannakoulia et al [19] found that the pattern characterized by consumption of vegetables, cooked meals, and eating dinner was inversely associated with BMI, WC, and the triceps skinfold, and the pattern characterized by consumption of whole-grain, legumes, and low consumption of sugar-sweetened drinks was inversely associated with the triceps skinfold.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…According to this theory, one way to reduce the currently observed high prevalence of obesity, involving lifestyle-related behaviors, is the reduction in the consumption of high energy-dense and nutrientpoor foods [31]. The lifestyle patterns of the Portuguese children were similar to those observed among Greek children and adolescents [19,22,23]. Yannakoulia et al [19] found that the pattern characterized by consumption of vegetables, cooked meals, and eating dinner was inversely associated with BMI, WC, and the triceps skinfold, and the pattern characterized by consumption of whole-grain, legumes, and low consumption of sugar-sweetened drinks was inversely associated with the triceps skinfold.…”
Section: Discussionmentioning
confidence: 86%
“…Vartanian et al [15] performed a meta-analysis of 88 articles and found significant associations between soft drink consumption and increased caloric intake and body weight. Milk and dairy products serve as one of the best sources of dietary calcium with high bioavailability [23], and they have consistently been associated with reduced body fat [35,36]. Skinner et al [35] monitored children beginning when they were 2 months old and found that the intake of dairy products was associated with a lower body fat percentage at 8 years old.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies have aimed to identify the occurrence of behavior patterns using PCA (6)(7)(8). Among them, Busch et al (6) identified four patterns among adolescents in the Netherlands: "behavior prone to risk" (alcohol consumption, smoking, drug use, and early sexual activity), "bully behavior" (bullying and compulsive use of the Internet), "problematic screen time" (excessive time using video games and internet), and "sedentary behavior, unhealthy eating habits, and insufficient physical activity" (excessive weekly time watching TV and using the internet, unhealthy eating habits, and insufficient physical activity).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, it has been shown that certain risk behaviors increase the risk of involvement in others, forming clusters of behaviors (6)(7)(8), that is, the occurrence of concurrent risk behaviors in adolescents (9,10). Simultaneity of different risk behaviors may have a synergistic effect on the deterioration of individual health; in other words, it may result in a multiplicative deleterious effect, rather than an additive effect of each behavior (11).…”
Section: Introductionmentioning
confidence: 99%